2002
DOI: 10.1046/j.1460-9568.2002.01945.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of amygdala neurons containing peptides and calcium‐binding proteins to fear‐potentiated startle and exploration‐related anxiety in inbred Roman high‐ and low‐avoidance rats

Abstract: The purpose of this study was to investigate amygdala‐related fear and anxiety in two inbred rat lines differing in emotionality (RHA/Verh and RLA/Verh), and to relate the behaviour of the animals to neuronal types in different nuclei of the amygdala. The behavioural tests used were the motility test, elevated plus‐maze and fear‐potentiated startle response. The neurons investigated were immunoreactive for the anxiogenic peptide corticotropin‐releasing factor (CRF‐ir), the anxiolytic peptide neuropeptide Y (NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 71 publications
3
29
0
Order By: Relevance
“…Subpopulations of GABAergic neurons in the amygdala express different CBPs and neuropeptides (Yilmazer-Hanke et al, 2002). We demonstrated that the density of PV containing neurons was significantly increased in the lateral nucleus of the amygdala of both EH and DEP rats compared with NH rats.…”
Section: Maternal Separation Increases the Density Of Pv-positive Intmentioning
confidence: 71%
See 2 more Smart Citations
“…Subpopulations of GABAergic neurons in the amygdala express different CBPs and neuropeptides (Yilmazer-Hanke et al, 2002). We demonstrated that the density of PV containing neurons was significantly increased in the lateral nucleus of the amygdala of both EH and DEP rats compared with NH rats.…”
Section: Maternal Separation Increases the Density Of Pv-positive Intmentioning
confidence: 71%
“…4) where the majority of amygdalar PV and CB positive GABAergic neurons are found (Yilmazer-Hanke et 2002). Oneway ANOVA revealed a significant main effect of separation of PV neuronal density in the lateral nucleus (F(2,25)=5.14; P=0.014) but not in the basal nucleus.…”
Section: Quantification Of Cbp Containing Neurons In the Amygdalamentioning
confidence: 90%
See 1 more Smart Citation
“…The extended amygdala (specifically the bed nucleus stria terminalis) is required for both CRFand stress-induced increases in startle (de Jongh et al, 2003;Gewirtz et al, 1998;Lee and Davis, 1997;Toufexis et al, this volume). Rats bred for differing levels of emotionality have been shown to differ in both CRF peptide levels in the amygdala and fear-potentiated startle performance, suggesting that these two markers may be linked (Yilmazer-Hanke et al, 2002). Indeed, CRF receptor activation in the amygdala appears to enhance consolidation of learned fear (Roozendaal et al, 2002), hence increased CRF tone in the amygdala may facilitate acquisition and/or extinction of FPS.…”
Section: Crf Effects On Startlementioning
confidence: 99%
“…Results from animal studies strongly suggest that different types of fear-conditioned behaviour are mediated by separate nuclei within the amygdala, and that the anxiogenic systems in the various nuclei may be differentially involved 84 . The basolateral complex (BL) of the amygdala seems to be significant for linking objects with current stimulusvalue, and the behaviours and goal-directed actions associated with the value 85 …”
Section: Conditioningmentioning
confidence: 99%